Biophilic Multisensory Perception In The Sense Of Well-Being Of Employees In A Corporate Environment - Belesa, Bruna Sardinha de Souza; Pinheiro, Ana Claudia Ribeiro; Pagel, Erica Coelho; Oliveira, Melissa Ramos da Silva (Technical and Scientific Journal Green Cities, 2025)
Given the growing concern about occupational stress and its adverse impacts on society’s mental health, this article proposes to explore an experimental approach to studying this problem, using the perspective of the study of perception as a basis for investigating interventions that can positively influence quality of life and promote mental health in work environments. The aim of this research is to assess the psychological well-being of employees in a corporate space when exposed to biophilic multisensory elements. The integration of multisensory elements in corporate spaces emerges as a possible strategy for promoting well-being, since it has the potential to modulate stress-related neurological responses. Therefore, this research seeks to study, through theoretical background and experimental results, the multisensory stimulus of Biophilic Design as an approach to promote the psychological well-being of workers, thus aligning itself with efforts to promote occupational health and prevent stress.